Passiontide : a novel - Roffey, Monique (Alfred A. Knopf, 2024)
"When a female musician is found murdered on a small tropical island, after a string of similar deaths, outraged local women take matters into their own hands. In this powerful new rewriting of the detective novel, Sora's death is the last straw and the beginning of something much larger, a revolution some are calling it. The event draws together four women who had never before seen each other as allies: a friend of the victim, the organizer of a sex workers' collective, a local activist, and the Prime Minister's wife. Tenderly, sometimes, hilariously, Passiontide chronicles how these women join forces and find new ways to help one another"--